2017
DOI: 10.2208/journalofjsce.5.1_157
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Force Acting on Bridge Girders

Abstract: This paper deals with how tsunami force acted on bridge girders when the Great East Japan Earthquake broke out on March 11, 2011. First of all, almost all data of bridge girders in the inundation area were collected. Satellite images in internet websites were introduced to make a quick survey on how many bridges were in the inundation area and how many of them were damaged. Detailed data on the bridges, such as dimensions and types, were obtained from authorities that have maintained those bridges. For damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…Their research study argued that although the maximum horizontal load and maximum uplift load applied on the bridge deck might not occur at the same time, it would be conservative to apply them simultaneously at the center of gravity (CG) of the deck. Other research studies [21] assumed that the hydrodynamic component of the tsunami loading is uniformly applied on the face of the bridge, meaning that in this case the resultant horizontal load would be applied at the mid-height of the bridge. This approach seems to be consistent with FEMA P-646 [38], which suggests that the hydrodynamic loading applied on the face of a building is uniform with height and the resultant force is applied at the mid-height.…”
Section: Application Of Maximum Horizontal and Vertical Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Their research study argued that although the maximum horizontal load and maximum uplift load applied on the bridge deck might not occur at the same time, it would be conservative to apply them simultaneously at the center of gravity (CG) of the deck. Other research studies [21] assumed that the hydrodynamic component of the tsunami loading is uniformly applied on the face of the bridge, meaning that in this case the resultant horizontal load would be applied at the mid-height of the bridge. This approach seems to be consistent with FEMA P-646 [38], which suggests that the hydrodynamic loading applied on the face of a building is uniform with height and the resultant force is applied at the mid-height.…”
Section: Application Of Maximum Horizontal and Vertical Forcesmentioning
confidence: 99%
“…In the 2004 Indian Ocean Tsunami, 81 bridges located on the coast of Sumatra were washed away [1]. In the 2011 Great East Japan Earthquake in Japan, many bridges were able to withstand the strong shaking; however, 252 bridges were washed away or moved by the tsunami [2]. The most severe and common type of failure in these bridges was the breaking of the connections between the superstructure and the substructure, which resulted in the unseating and wash out of the bridge deck by the tsunami waves ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent tsunami events; however, demonstrated that such structures are vulnerable to the tsunami-induced loading. In fact, the 2004 Indian Ocean Tsunami washed away 81 bridges on the coast of Sumatra [1], while the tsunami generated by the 2011 Great East Japan earthquake damaged 252 bridges [2]. The most severe and common type of failure in these bridges was the breaking of the connections between the superstructure and the substructure, which resulted in the unseating and wash out of the bridge deck by the tsunami waves.…”
Section: Introductionmentioning
confidence: 99%
“…These studies included (i) on-site surveys and damage analysis [3][4][5], (ii) small-scale wave flume experiments [6][7][8][9][10], and (iii) numerical simulations [11][12][13][14][15][16]. Several studies focused on the tsunami loads on flat slabs [8], while other studies examined more complex geometries such as decks with girders [2,7,17]. Most of the experimental studies were conducted at small to medium scales, ranging from 1:100 to 1:20, and the bridge models consisted of acrylic or wood decks supported rigidly, either from the top or the bottom of the deck, without considering the actual flexibility or inertia of the bridge.…”
Section: Introductionmentioning
confidence: 99%